LIFESTYLE WITH HYPERTENSION AT WILKER PUSKESMAS WESAPUT - Sethiana Dewi Ruben; Santalia Banne Tondok; Suningsih Suabey; Rosdiana Tandiola (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
Controlling lifestyle and behavioral factors by implementing a healthy lifestyle can prevent hypertension. The aim of the study was to determine the relationship between lifestyle (smoking, physical activity, coffee consumption, fat consumption) and the incidence of hypertension at the Wesaput Community Health Center. Observational analytical research design, cross sectional approach, sample of 35 respondents, simple random sampling. Data collection uses questionnaires and sphygmomanometers. Data were analyzed using the chi-square test. The research results showed that the lifestyle that was related to the incidence of hypertension was fat consumption ( p = 0.015). Meanwhile, there was no relationship between lifestyle and the incidence of hypertension, namely smoking habits (p = 0.207), physical activity (p = 0.226) and coffee consumption (p = 0.490). It was concluded that there was a relationship between lifestyle (fat consumption) and the incidence of hypertension, there was no relationship between lifestyle (smoking habits, physical activity and coffee consumption) and the incidence of hypertension. It is hoped that people will check their blood pressure regularly and adopt a healthy lifestyle. It is recommended that health workers provide health education/counseling regarding a healthy lifestyle.